RELASI IDENTIK ANTARA SEPAKBOLA DENGAN PENDIDIKAN ISLAM - Adi, Nugroho Prasetya; Hasani, Zhul Fahmy; El Syam, Robingun Suyud (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
Football has become one of the most popular spectator sports on the planet. It not only offers match attractions on the field, but also offers a series of rituals and euphoria of togetherness for the audience. Therefore, a review is needed to understand how football is linked to the Islamic religion. This research aims to review the identical relationship between football and Islamic education. A systematic and transparent framework was used to search, select and report relevant articles. This research synthesizes a collection of identified articles using library analysis, where each article is identified to see its relevance. This study concludes that football is identical to the teachings of the Islamic religion, where the spirit of sportsmanship is the rule of the game that must be obeyed in football, and piety is a symbol of religious obedience. Obedience to religious rules or values ​​is the result to be achieved in Islamic education. This report highlights future research avenues and identifies gaps in the field of Islamic education in football. Research implications, Islamic education researchers in football and senior practitioners can use this literature review to review the current football and religion literature. This can also be useful for non-Islamic education researchers who intend to conduct multidisciplinary research. This research looks at the literature on Islamic education in football by considering the latest literature and a fresh perspective.